2022
DOI: 10.1038/s41591-022-01851-x
|View full text |Cite
|
Sign up to set email alerts
|

Personalized response-directed surgery and adjuvant therapy after neoadjuvant ipilimumab and nivolumab in high-risk stage III melanoma: the PRADO trial

Abstract: A djuvant immune checkpoint inhibition (CPI) and BRAF/ MEK-targeted therapies after therapeutic lymph node dissection (TLND) have improved relapse-free survival (RFS) in patients with clinical stage III nodal melanoma. Despite these improvements, approximately 40-50% of patients have a relapse within 3-5 years after TLND 1-3 . Preclinical and early clinical trial data suggest that neoadjuvant CPI leads to superior anti-tumor immunity and survival benefit compared to adjuvant CPI 4,5 . Similarly to stage IV mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(142 citation statements)
references
References 35 publications
(70 reference statements)
1
129
0
1
Order By: Relevance
“…The 24-month RFS and distant metastasis-free survival rates were 93% and 98%, respectively, in this cohort of patients with MPR. 35 In both reported cohorts, patients received only two doses of ipilimumab and nivolumab, and it is possible that additional systemic therapy may have further deepened the histologic response. Overall, the results strongly support continued exploration of the concept of using the ILN status to support omission of lymphadenectomy in carefully selected patients undergoing neoadjuvant immunotherapy.…”
Section: Melanomamentioning
confidence: 99%
“…The 24-month RFS and distant metastasis-free survival rates were 93% and 98%, respectively, in this cohort of patients with MPR. 35 In both reported cohorts, patients received only two doses of ipilimumab and nivolumab, and it is possible that additional systemic therapy may have further deepened the histologic response. Overall, the results strongly support continued exploration of the concept of using the ILN status to support omission of lymphadenectomy in carefully selected patients undergoing neoadjuvant immunotherapy.…”
Section: Melanomamentioning
confidence: 99%
“…Recently approved immune checkpoint inhibitors (ICI) immunotherapies have completely changed the treatment of CM with significantly improved survival rate and disease lasting control ( Hodi et al, 2018 ; Hamid et al, 2019 ). However, the response rate to ICI is still limited ( Reijers et al, 2022 ). Therefore, further efforts should be made to maximize the efficacy of ICI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of any approach to omit lymphadenectomy in good responders to neoadjuvant therapy can reasonably be conceived as recapitulating the currently accepted standard applied to the management of sentinel‐node positive melanoma: an acceptable rate of regional node basin failure (e.g., under 30%) with few if any patients developing uncontrolled nodal disease and no adverse impact on overall survival 17,18 . Data from the recently completed PRADO study provides strong evidence to assess the feasibility of this approach in patients willing to comply with an active surveillance protocol 22 …”
Section: Is Completion Dissection Still Necessary For Clinically Node...mentioning
confidence: 99%
“…17,18 Data from the recently completed PRADO study provides strong evidence to assess the feasibility of this approach in patients willing to comply with an active surveillance protocol. 22 Until this prospective trial data matures and ideally is confirmed in other centers' experience, the standard operation for most stage III melanoma treated with neoadjuvant therapy remains a radical lymphadenectomy using the same surgical principles that would govern the operation performed in the absence of systemic treatment. Since there are still many unanswered questions about neoadjuvant therapy-including the optimal therapeutic agent, duration of treatment, impact on long-term regional and distant relapse-free survival, and whether there is any overall survival advantage compared to surgery followed by adjuvant therapy-our strong preference is to enroll these patients onto prospective clinical trials whenever possible, but we now routinely offer this approach to patients with clinical stage III melanoma off-study as standard of care treatment.…”
Section: ×) (B) High-power View Of Area Of Inflammation Showing Nonca...mentioning
confidence: 99%